The effect of the demographic characteristics of the students of the first cycle of basic education on the process of visual perception - premature students enrolled in the education of the South Sharqiyah Governorate - Alalwi, Hanan Faiz Mubark; Alghafri, Ali Salim Rashid (Journal of Educational and Psychological Sciences, 2022)
The study aimed to trace the relationship between visual perception and the working memory capacity of preterm students in the first cycle of basic education. The study sample numbered 40 participants who met the conditions of study for preterm students. The study chose the correlational approach as its methodology. The study also used two research tools. First: The complex shape test of image A was measured by using the technique of honesty of the arbitrators, and its stability through the test- retest, which is worth equal 0.934. The second tool consisted of an image recognition test. Was measured by using the technique of honesty of the arbitrators, and its stability through the test- retest, which is worth equal 0.807.The study concluded that there was not a significant correlation between the visual perception and the working memory. It also found that the type of production of the participants in the study of type I, and by obtaining this type 27.5 % of proportion. Moreover, 48.6% of the participants in the study reached the capacity of their working memory to 7. The study recommended that the families should be aware of the importance of developing and enriching the higher cognitive processes such as visual awareness through the provision of home games to help develop this process.
Keywords: demographic characteristics; basic education; visual perception; premature students